Physical and biological controls of algal blooms in the Río de la Plata - Silva, C.; Marti, Clelia; Imberger, J. (2014)
© 2014, Springer Science+Business Media Dordrecht. Coupled three-dimensional hydrodynamic and ecological numerical simulations were used to investigate the role of transport, stagnation zones and dispersion on inter-annual blooms of the diatom Aulacoseira sp. in the vicinity of the drinking water intakes of the Buenos Aires city (Argentina) in the upper Río de la Plata. Three different summer events were analyzed. First, a mild biomass bloom year (2006–2007), second, a high biomass bloom year (2007–2008) and third, a “normal” no bloom year (2009–2010). Simulated water height, water temperature, suspended solids and chloroph yll (formula presented.) concentrations patterns compared well with field data. Results revealed that the advection of phytoplankton cells via inflows to the Río de la Plata triggered Aulacoseira sp. blooms in the domain. In addition, excessive growth observed near the drinking water intakes, along the Argentinean margin, were associated with long retention times (stagnant region) and weak horizontal dispersion. Increased concentrations of suspended solids in the water column, in response to re-suspension events, did not prevent the blooms, however, were found to also play a key role in controlling the rate of phytoplankton growth. Finally, a non-dimensional parameter, R, that considers phytoplankton patch size, e-folding growth and dispersion time scales is shown to determine the potential bloom occurrences, as well as bloom intensity; R values higher than 5.7 suggest intense phytoplankton growth. For the mild biomass bloom year, (formula presented.), for the high biomass bloom year, (formula presented.) and for the “normal” no bloom year (formula presented.).